A dual-channel incoherent broadband cavity-enhanced absorption spectrometer for sensitive atmospheric NOx measurements. Issue 8 (31st March 2021) - Pakkattil, Anoop; Saseendran, Aiswarya; Thomas, Arun P.; Raj, Anjana S.; Mohan, Ardra; Viswanath, Deepa; Chatanathodi, Raghu; Varma, Ravi
Abstract : A novel dual cavity UV-VIS spectrometer for sensitive monitoring of urban NO x and other interfering pollutants. Abstract : We describe and characterize a dual-channel incoherent broadband cavity-enhanced absorption spectrometer (DC-IBBCEAS) for the sensitive measurements of NO x : the sum of nitrogen monoxide (NO) and nitrogen dioxide (NO2 ) in the atmosphere. The instrument employs two 1 m long optical cavities, with air being extracted from a common sampling line. The first channel (cavity-1) spans 340–380 nm and the second channel (cavity-2) spans the 405–460 nm spectral range, both measuring NO2 simultaneously. High absorption cross-sections of NO2 in both channels are effectively utilized for its sensitive quantification. NO is quantified by titrating it with ozone to NO2 in channel-2, where the difference of NO2 measured from that in channel-1 corresponds to the NO concentration in the sampled air. The instrument offers 1-ppb detection sensitivity for both NO and NO2 with a maximum possible uncertainty of ∼9%. The use of close yet different spectral regions in the two channels readily extended measurements to a broader range without compromising its sensitivity to NO x quantification. This would extend the DC-IBBCEAS applicability to simultaneously monitor interfering species with significant absorption cross-sections in the region in either channel, such as glyoxal (CHOCHO), methylglyoxal (CH3 COCHO), and nitrous acid (HONO).